Human Development Index and Regional Development: Measuring Human Welfare Beyond Economic Growth - Saiful Lana; Cevin Lula (IJED: International Journal of Economy Development Research, 2025)
Economic development has traditionally been measured through indicators such as gross domestic product (GDP) and income per capita. However, these indicators often fail to capture the broader dimensions of human welfare. The Human Development Index (HDI) was introduced by the United Nations Development Programme (UNDP) as a multidimensional measure of development that incorporates indicators of health, education, and living standards. This study aims to examine the importance of the Human Development Index in evaluating development performance and to analyze its role in assessing regional human welfare. Using a qualitative approach based on literature review and secondary data analysis, this study explores the conceptual framework of HDI and its implications for development policy. The findings indicate that HDI provides a more comprehensive perspective on development compared to traditional economic indicators. By integrating education, health, and income dimensions, HDI enables policymakers to identify development gaps and formulate more inclusive development strategies. The study concludes that HDI remains an essential tool for measuring human development and guiding sustainable and equitable development policies.